Influence of rotation on cascade processes in helical turbulence - Shestakov, Aleksandr Vladimirovich; Stepanov, Rodion Aleksandrovich; Frick, Petr Gotlobovich (Computational Continuum Mechanics, 2012)
The paper discusses various ways of describing the action of the Coriolis force in the framework of shell models for developed helical turbulence. The influence of rotation on the process of spectral energy and helicity transfer in turbulent flow is studied. It is shown that the rotation slows down the transfer cascade, thereby reducing the rate of decay of turbulence and leads to steeper spectra.